2017
DOI: 10.3233/bmr-169781
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shockwave therapy vs. kinesiotherapy for osteoarthritis of the knee: A pilot randomized controlled trial

Abstract: ESWT improves WOMAC and ROM better then KIN on the affected knee in patients with OA of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 22 publications
0
52
0
Order By: Relevance
“…The sample size ranged from 18 to 160. All experimental groups received ESWT, while control groups received different treatments including placebo [22,23,25,26,28,30,34,48,49,51,52], medication [31,32,43,44,50], intra-articular injections [21,26,27,29,35,36,39,40], traditional Chinese medicine [38,41,42,45,2 BioMed Research International 46], ultrasound [22,24,47], surgery [33], and kinesiotherapy (KIN) [37].…”
Section: Statisticalmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size ranged from 18 to 160. All experimental groups received ESWT, while control groups received different treatments including placebo [22,23,25,26,28,30,34,48,49,51,52], medication [31,32,43,44,50], intra-articular injections [21,26,27,29,35,36,39,40], traditional Chinese medicine [38,41,42,45,2 BioMed Research International 46], ultrasound [22,24,47], surgery [33], and kinesiotherapy (KIN) [37].…”
Section: Statisticalmentioning
confidence: 99%
“…Only temporary pain, minor bruising, or transient soft tissue swelling was observed in nine studies [25,30,34,42,44,47,[50][51][52]. No adverse events were observed during the treatment in other six studies [27,29,[36][37][38]46], and the remaining studies did not mention it.…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…Another randomized controlled trial showed that ESWT can improve WOMAC and range of motion (ROM) better than kinesiotherapy (KIN) on knee OA [54]. Further, a retrospective study [49] showed that compared with laser therapy, patients underwent ESWT showed greater effect in symptoms relief with regard to WOMAC and Numeric Rating Scale (NRS) evaluation, while no adverse events occurred in both groups.…”
Section: Extracorporeal Shockwave Treatment For Osteoarthritismentioning
confidence: 99%
“…An in vitro study [ 53 ] explained that ESWT could increase the activity of chondrocytes through inducing the surface expression of major hyaluronan cell receptor CD44, which could allow the increase of Collagen type 2A/ Collagen type 1A (COL2A/COL1A) ratio when using HA, and this could enhance the cell susceptibility of chondrocytes to HA, favoring the repair of degenerated cartilage. Another randomized controlled trial showed that ESWT can improve WOMAC and range of motion (ROM) better than kinesiotherapy (KIN) on knee OA [ 54 ]. Further, a retrospective study [ 49 ] showed that compared with laser therapy, patients underwent ESWT showed greater effect in symptoms relief with regard to WOMAC and Numeric Rating Scale (NRS) evaluation, while no adverse events occurred in both groups.…”
Section: Extracorporeal Shockwave Treatment For Osteoarthritismentioning
confidence: 99%
“…Thus, while evidence supports combined interventions for thumb OA, we are unable to make specific recommendations regarding combined interventions for knee OA, or for other affected joints. With respect to adjunct interventions, we found evidence to support the use of tape for knee OA 21,55,57 , assistive devices for hand OA 59 , thumb splints for thumb OA 60 , manual therapy for knee OA 23,45,47,53 and neck OA 65 , acupuncture for knee OA 44 , and electrophysical agents for knee OA 19,22,48 (Tables III and IV), while conflicting evidence was found for transcranial direct current stimulation (tDCS) 30,37 (Table IV). Taken together with established clinical guidelines, our findings reinforce that these interventions should be adjuncts to accompany core recommended interventions for OA, rather than be used as standalone or key treatments 2,3,9e16 .…”
Section: Discussionmentioning
confidence: 99%